(3ebGQHI dJMbjb GdejRI GdJfGaSjI s - (3NGdO(B, (3bGTjs ((3GdLRGFQ (B:s (3OGQ CLjGd GdQbej (B,s, 2023)
(3jJfGhd GdcJGH GdJCUjd GdfXQj ddeSDhdjI GdGLJeGYjI ddeDSSGJ HeG ajgG Gdeaghe hGdJWhQ GdJGQjNj hGdCgejI, GdejRI GdJfGaSjI JMOj GdeDSSGJ GdeYGUQI h JMdjd JCKjQ CHYGO GdeSDhdjI GdGLJeGYjI ddeDSSGJ Ydi JMbjb GdejRI GdJfGaSjI eY PcQ feGPL Yf eDSSGJ YGdejI JWHb GdeSDhdjI GdGLJeGYjI(B. s
Keywords: (3EOGQI GdCYeGds; (3GdGSJQGJjLjI GdJfGaSjIs; (3GdeSDhdjI GdGLJeGYjIs